Synthesis, characterization, quantum chemical calculations and antioxidant activity of new bis-isatin carbohydrazone and thiocarbohydrazone derivatives - Muğlu, Halit; Çavuş, M. Serdar; Bakır, Temelkan; Yakan, Hasan (Elsevier BV, 2019)
Abstract 1,5-Bis(5-chloro-2-oxoindolin-3-ylidene)thiocarbohydrazone (3), 1,5-Bis(5-metoxy-2-oxoindolin-3-ylidene)thiocarbohydrazone (4), 1,5-Bis(5-metoxy-2-oxoindolin-3-ylidene)carbohydrazone (5) were obtained from isatins and thio/carbohydrazides under reflux in absolute ethanol. The structures of these synthesized compounds were determined using FT-IR, 1H NMR, 13C NMR spectroscopy, and elemental analysis. Quantum chemical calculations were also performed at B3LYP/6-311++G(2d,2p) level in order to obtain information about the molecular geometries and electronic data, such as HOMO-LUMO energy eigenvalues and density of states (DOSs). In addition, structural and antioxidant properties of the compounds were studied theoretically. QTAIM analysis was performed to investigate the relationship between intramolecular interactions, electronic data and antioxidant activity. The in vitro antioxidant activity of all the compounds was determined by 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radical scavenging method. Antioxidant activity was followed by Ascorbic acid > 3 > 4 > 5.
Keywords: Isatin; Antioxidant activity; QTAIM; Carbohydrazide; DFT; Spectroscopic techniques